PENGARUH PENGGUNAAN SOFTWARE MYOB SEBAGAI MEDIA PEMBELAJARAN DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR AKUNTANSI PERUSAHAAN JASA DI SMA - Usdekti, Sri; Murbojono, Rahmat; Suratno, Suratno (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2012)
This research is motivated persistence of low learning outcomes accounting, lack of use of computer-based instructional media that support the activity and participation of students in the learning process accounting. One way to overcome this problem is to use MYOB software as a learning medium accounting to assist the teacher in the learning condition of innovative accounting. This study aims to determine the effect of using MYOB software media on learning outcomes accounting services company, and reveal the influence of student interest to the learning outcomes of accounting and how the interaction between media use MYOB, interest in learning and learning outcomes of accounting. The method used in this study is the experimental method, the study population was all students of class XI IPS SMAN 4 Jambi. Samples were taken by random sampling technique as many as 80 students. Data collection techniques for variable interest learns using questionnaires and to learn to use the test variable results. The validity of the test was tested with ITEMAN program and for data analysis using ANOVA technique 2 Land with prerequisite distribution normality test data using Lilliefors models, and test of homogeneity of variance using Bartlett's test, with a significance level of 5% research. Results calculated with SPSS 16, shows that the distribution of the data according to the normal curve, the sample is derived from a homogeneous population. Demonstrated that: (1) the results of the study group of students who were given learning with media MYOB higher compared with a group of students who were given learning with media LKS (Fhitung 1.362> 0.05); (2) Results of study accounting services firm group of students who have a high interest in learning, better when compared with the results of studying accounting services company in the group of students who have a low interest, both of which are taught using MYOB software media and the use of media LKS because of F 0.761> 0 , 05. (3) In the group of students who have a high interest in learning, learning outcomes accounting services firms students taught using MYOB software media is higher when compared with the results of studying accounting services firms students taught using media LKS (4) In the group of students who have interest in learning low, the result of learning accounting services firms students taught using MYOB software media is higher when compared with the results of studying accounting services firms students taught using LKS media. (5) There is an interaction between media software MYOB and interest in learning on learning outcomes Fhitung services firms accounting for 0.752, for p> 0.05. Keyword: Keywords: Software MYOB, interest in learning, learning outcomes accounting services company.